(untitled) - McBee, Jim (San Francisco, 2002)
This guide to Exchange 2000 Server covers issues such as integrating migration, backup and recovery, streamlining daily maintenance, client and server automation, and securing servers against attack.
Keywords: Client/server computing,Quan hệ máy chủ/ máy con